Analysis of Health-Based Transportation System for Health Transformation in DKI Jakarta - Deyo Alfa Christian; Adang Bachtiar; Cicilya Candi (International Journal Labs, 2023)
The quality of transportation in big cities, especially in DKI Jakarta faces many challenges, such as high population creating traffic congestion, air pollution, and access to public transportation. Currently, DKI Jakarta has a population of 10.67 million in 2022 and is ranked 38 out of 60 countries with good public transportation, the development of health-based transportation that is effective in reducing health impacts, infrastructure and urban design are important in supporting high mobility. An important aspect of improving transportation in big cities is the development of sustainable public transportation systems. Using the PRISMA extension for Scoping Review (PRISMA-ScR) guidelines, 93 articles published between 2000 and 2022 met the inclusion criteria looking at Health-based transport, Urbanization, and Policy. Health-based transportation is very important to be addressed by encouraging sustainable development, green transportation, good urban planning to data-driven policy making, utilizing data and technology, can contribute to public health and a healthier and more livable urban environment, this still requires collaborative efforts from the government, policy makers, and the community to create an efficient and sustainable transportation system in DKI Jakarta